2012
DOI: 10.1158/0008-5472.can-12-0736
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Molecular and Biological Assessment of an Erlotinib-Resistant Lung Adenocarcinoma Model Reveals Markers of Tumor Progression and Treatment Response

Abstract: Lung cancer patients with activating mutations in the epidermal growth factor receptor (EGFR) kinase who are treated long-term with tyrosine kinase inhibitors (TKIs) often develop secondary mutations in EGFR associated with resistance. Mice engineered to develop lung adenocarcinomas driven by the human EGFR T790M resistance mutation are similarly resistant to the EGFR TKI erlotinib. By tumor volume endpoint analysis, these mouse tumors respond to BIBW 2992 (an irreversible EGFR/HER2 TKI) and rapamycin combinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
(38 reference statements)
2
31
0
Order By: Relevance
“…2E). Our observations are supported by previous observations that β-catenin-TCF/LEF target genes such as cyclin D1 and c-Myc are upregulated in NSCLC harboring EGFR-T790M (23, 40). Inhibition of serine/threonine phosphorylation by GSK3β is a well-recognized mechanism of β-catenin stabilization (8).…”
Section: Discussionsupporting
confidence: 91%
“…2E). Our observations are supported by previous observations that β-catenin-TCF/LEF target genes such as cyclin D1 and c-Myc are upregulated in NSCLC harboring EGFR-T790M (23, 40). Inhibition of serine/threonine phosphorylation by GSK3β is a well-recognized mechanism of β-catenin stabilization (8).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, EGFR has been also shown to regulate the antioxidant transcriptional factor Nrf2 by increasing its activity in lung cancer cells. In these cells, EGFR/Nrf2 favors cell proliferation, tumor progression and resistance to chemotherapies [50][51][52]. Our data showed that MK2 is involved in EGFR activation and regulates Nrf2 in a positive way.…”
Section: Discussionmentioning
confidence: 57%
“…Microarray expression profiling of the mouse T790M/L858R (TL) tumors as compared to controls revealed increased levels of Pd-1 , Pd-l1 ( Cd274 ), Ctla-4 , Il-6 , Tgf-β1 , and granulin ( Grn ) along with ligands for the EGFR (EGFR mutant vs WT for the gene set shown p=3×10 −20 ) (Fig 1a). Analysis of microarray data from previously reported datasets showed no significant differences in Pd-l1 and Pd-l2 expression among tumors derived from multiple models of EGFR-driven lung adenocarcinoma (L858R, L858R/T790M (TL) and Exon 19 deletion/T790M (TD)) (17, 18), indicating that EGFR-driven tumors of a variety of EGFR mutations display elevated Pd-l1 and Pd-l2 expression as compared to normal lung (data not shown). We next confirmed the expression of PD-L1 on tumor (CD45 − humanEGFR + ) and associated hematopoietic cells by flow cytometry and immunohistochemistry in EGFR-driven mouse lung adenocarcinomas (IHC) (Fig 1b, Supplementary Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Expression data from wild type and EGFR transgenic mice were obtained from a previous study (18) and converted into log2 values. Pearson correlation coefficient p values were calculated by comparing expression values for each transcript over all samples to either PD-L1 or PD-1 expression.…”
Section: Methodsmentioning
confidence: 99%